2015
DOI: 10.1039/c5ra00838g
|View full text |Cite
|
Sign up to set email alerts
|

Ag-modified AgI–TiO2 as an excellent and durable catalyst for catalytic oxidation of elemental mercury

Abstract: was employed for the removal of elemental mercury (Hg 0 ) from flue gas, and extra elemental silver (Ag) was introduced to enhance the catalytic activity and stability. AgI-TiO 2 displayed an excellent effect on Hg 0 catalytic oxidation, and the Hg 0 oxidation efficiency was almost 100% with only 5 ppm HCl at 350 C, which was better than that of KI-Ti. Adding Ag to AgI-TiO 2 can notably prolong the period of high efficiency, and the Hg 0 oxidation efficiency was still above 90% after 10 h with only 2% Ag added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Since β-AgI nanocrystals were reported to exhibit much higher visible light absorption than AgI colloid (β-AgI and γ-AgI mixture), it is possible that the PEC properties of AgI/TiO 2 -NTs will probably be regulated due to different β/γ-AgI ratio. Besides, peaks corresponding to Ag 0 species were not observed by XRD in the present study. , …”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…Since β-AgI nanocrystals were reported to exhibit much higher visible light absorption than AgI colloid (β-AgI and γ-AgI mixture), it is possible that the PEC properties of AgI/TiO 2 -NTs will probably be regulated due to different β/γ-AgI ratio. Besides, peaks corresponding to Ag 0 species were not observed by XRD in the present study. , …”
Section: Resultscontrasting
confidence: 65%
“…Besides, peaks corresponding to Ag 0 species were not observed by XRD in the present study. 33,34 To further corroborate the surface chemical state of AgI, XPS spectra were used to investigate the Ag 3d and I 3d on AgI/ TiO 2 -NTs350. As shown in Figure 2A, two peaks of Ag 3d located at 367.9 eV (Ag 3d 5/2 ) and 373.9 eV (Ag 3d 3/2 ), which were very similar to the reported values for β-AgI.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Importantly, recent works have led to the development of AgI-based composite photocatalysts demonstrating efficient absorption of visible light and suppression of recombination of photogenerated charge carriers. For example, it has been reported that AgI/SiNW [8], AgI/ZnO [9], AgI/TiO 2 [10] can effectively accelerate the separation of photogenerated charge carriers due to the strong interface electric field by band-edge offset. However, the point contact caused by these bulk phase recombination could lead to low conjunctions of AgI with semiconductors, which could limit the photo-induced charge separation.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor photocatalysts harvest the energy of incoming photons to drive chemical reactions for solar-to-fuel conversion and environmental remediation, including hydrogen (H 2 ) energy generation, [1][2][3] water treatment, [4][5][6][7][8][9][10][11] air purification, 12,13 ammonia (NH 3 ) synthesis, 14,15 carbon dioxide (CO 2 ) reduction 16,17 and warfare agents destruction. 18,19 In land-mark studies, Fujishima 20 and Carey 21 reported production of clean H 2 energy and degradation of organic pollutants by semiconducting titanium dioxide (TiO 2 ) under UV light irradiation, respectively.…”
Section: Introductionmentioning
confidence: 99%